Peningkatan Keterampilan Sikat Gigi yang Baik dan Benar pada Santri TPA Masjid Taslim Tegal Kenongo (Kegiatan Pengabdian Bekerja Sama dengan Karang Taruna Padukuhan Tegal Kenongo) - M. Shulchan Ardiansyah; Fara Amrina Revada; Bella Pardian Nur Allifiah; Aulia Fadillah (Dental Agromedis, 2024)
Children are a group that is vulnerable to dental disease, because generally children have behaviors or habits that are not in accordance with what is recommended. To improve dental and oral disease prevention programs in children, a series of programs are needed both at school, in the family environment, and in the surrounding environment. One of the series of programs is the effort to form cadres as an effort to improve the dental and oral health status of children. From the results of interviews with Tegal Kenongo Padukuhan youth, it was conveyed that a group of students had formed dental and oral health cadres which were filled with activities that could improve the quality of dental and oral health by carrying out dental health education training and how to brush their teeth properly. However, there has been no follow-up after the training event. Therefore, the community service this time intends to reactivate the dental health cadres that have been formed by carrying out activities to improve the dental and oral health of TPA Taslim Mosque students by being given counseling on correct toothbrushes, pretest and posttest as well as correct tooth brushing practices which are contested will be assessed by health cadres from the Tegal Kenongo youth group. This is indirectly expected to improve the quality of children's dental health.Keywords: Children, dental and oral health, brushing teeth properly.